Analysis of Some Aspects of Students’ Attitudes Towards Technical Vocational Education: an Empirical Study - Vasilev, Iliyan; Rusinov, Stoycho (Педагогически форум, 2025)
This article examines some of the attitudes of students towards Technical Vocational Education and Training (TVET) in Bulgaria, focusing on the factors influencing their motivation, organizational forms of training, assessment mechanisms and the level of student engagement. In the context of a lack of permanent, systematic and nationally representative periodic surveys, the authors analyze a large-scale sample of students (1042 twelfth graders in TVE). Based on the results, the importance of personalized educational approaches and the implementation of innovations in VET curricula is emphasized, which form the basis of the author’s STRONG model, developed within the framework of the dissertation research of one of the co-authors. The study also aims to identify student attitudes and perceptions about the adequacy of training to the needs of the labor market and additional opportunities for the development of talented students. The results demonstrate categorical negative attitudes, expressed in a low assessment of the system, as well as the need for significant reforms in the educational structure at the level of vocational education in Bulgaria.